A Bioinspired Method for Optimal Task Scheduling in Fog-Cloud Environment - Anka, Ferzat; Tejani, Ghanshyam G.; Sharma, Sunil Kumar; Baljon, Mohammed (Tech Science Press, 2025)
Due to the intense data flow in expanding Internet ofThings (IoT) applications, a heavy processing cost and workload on the fog-cloud side become inevitable. One of the most critical challenges is optimal task scheduling. Since this is an NP-hard problem type, a metaheuristic approach can be a good option. This study introduces a novel enhancement to the Artificial Rabbits Optimization (ARO) algorithm by integrating Chaotic maps and Levy flight strategies (CLARO). This dual approach addresses the limitations of standard ARO in terms of population diversity and convergence speed. It is designed for task scheduling in fog-cloud environments, optimizing energy consumption, makespan, and execution time simultaneously three critical parameters often treated individually in prior works. Unlike conventional single-objective methods, the proposed approach incorporates a multi-objective fitness function that dynamically adjusts the weight of each parameter, resulting in better resource allocation and load balancing. In analysis, a real-world dataset, the Open-source Google Cloud Jobs Dataset (GoCJ_Dataset), is used for performancemeasurement, and analyses are performed on three considered parameters. Comparisons are applied with well-known algorithms: GWO, SCSO, PSO,WOA, and ARO to indicate the reliability of the proposed method. In this regard, performance evaluation is performed by assigning these tasks to VirtualMachines (VMs) in the resource pool. Simulations are performed on 90 base cases and 30 scenarios for each evaluation parameter.The results indicated that the proposed algorithm achieved the bestmakespan performance in 80% of cases, ranked first in execution time in 61% of cases, and performed best in the final parameter in 69% of cases. In addition, according to the obtained results based on the defined fitness function, the proposed method (CLARO) is 2.52% better than ARO, 3.95% better than SCSO, 5.06% better than GWO, 8.15% better than PSO, and 9.41% better thanWOA.
Keywords: Improved ARO; Fog Computing; Task Scheduling; Gocj_Dataset; Chaotic Map; Levy Flight